Ötekini Algılama Bağlamında Dinî Gruplar Arası İlişkiler - Yapıcı, Asım (Dinî araştırmalar, 2002)
Nowadays, the dialogue between the cultures, beliefs and civilisations has gained a very important position in the world. However, every group has a distinctive social identity and this may conclude that the others are negative according to them. This situation is a serious handicap for both the dialogue between the religions and sects. In this article, we have tried to investigate how to struggle against the phenomenon like prejudice and stereotypes which impede the dialogue among the religions and beliefs. So, we wanted to transfer the theoretical foresights and empirical results which socio-psychological researchs produced, to the issue of the dialogue between the religions